Prevalence, management and complications of diabetic patients in pabna city - Parvez, G M Masud; Rumayesha; Parvin, Mst. Shanzida; Afrin, Aziza; Azad, Abul Kalam; Aktar, Mst. Mahabuba; Rabbi, Md. Fazle; Rashid, Sumaiya; Farjana, Akila; Naznin, Most. Anika; Sultana, Razia; Parvin, Shumaia; Kader, Md. Abdul (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
Diabetes is one of the leading causes of death and its prevalence is increasing day by day. This survey was conducted by direct interviewing to the diabetic patients. In this study, the interviewees were the diabetic affected patients of Pabna district. About 1100 persons were interviewed among them 37.55% were male and 62.45% were female. Most of the patients have onset of diabetes at 41-50 years age. Most of our observed patients have suffered from diabetes between 1-5 years (62.64%) followed by 6-10 years (25.18%). Here 3.18% patients have BMI â‰¤18.5, 47.55% have between 18.5-24.9, 39.55% have BMI 25.5-29.9 and 9.73% have BMI â‰¥30. Here 93.45% diabetic patients have blood glucose level of >7 mmol/L. The diabetic patients also suffered from retinopathy 50.36%, neuropathy 19.73%, nephropathy 23.55% and foot problem 43.36%. About 63.27% are taking diet, 56.91% are taking exercise and 93.91% are taking drug for treating diabetes. It was found that the patients are suffering from different other diseases. The patients need to be aware about the potential risk of other diseases.